Penerapan Metode Read-Aloud Pada Perkembangan Literasi Anak Usia Dini Di Kober Miftahul Hidayah Bayongbong Garut - Wardani, Elia; alwah syamsiah, Ai (LP2M STAI Al-Musaddadiyah Garut, 2022)
The low interest in literacy in education in Garut district is the background of this research, so that researchers have a goal to reveal how the development of early childhood literacy when applying the Read-Aloud method using the Kemmis & Mc Taggart. Class Action Research (CAR) method. Data collection techniques through interviews, observation and documentation. How to analyze data with data reduction, display data and draw conclusions The subjects of this study were 20 students aged 3-4 years in Kober Miftahul Hidayah Bayongbong. The research was carried out for 3 cycles of 9 meetings, the indicator stages that appeared to be developing were being able to answer simple questions, able to read and write beginnings, fluent in vocal pronunciation, intonation and expression, able to express the content of messages conveyed in books, and the last interest was listening to stories with Maintain reading attention for 10-15 minutes. Based on the results of the study, the overall application of the read-aloud method proved effective in improving the development of early childhood literacy. Both ages 3.0-3.11 or 4.0-4.11 are both very effective to apply the read-aloud method both at school and educators or at home and parents. Keywords: development; Literacy; Read-Aloud method.